Confucian Iconoclasm - Major, Philippe (State University of New York Press, 2024)
Confucian Iconoclasm proposes a novel account of the emergence of modern Confucian philosophy in Republican China (1912–1949), challenging the historiographical paradigm that modern (or New) Confucianism sought to preserve traditions against the iconoclasm of the May Fourth Movement. Through close textual analyses of Liang Shuming's Eastern and Western Cultures and Their Philosophies (1921) and Xiong Shili's New Treatise on the Uniqueness of Consciousness (1932), Philippe Major argues that the most successful modern Confucian texts of the Republican period were nearly as iconoclastic as the most radical of May Fourth intellectuals. Questioning the strict dichotomy between radicalism and conservatism that underscores most historical accounts of the period, Major shows that May Fourth and Confucian iconoclasts were engaged in a politics of antitradition aimed at the monopolization of intellectual commodities associated with universality, autonomy, and liberty. Understood as a counter-hegemonic strategy, Confucian iconoclasm emerges as an alternative iconoclastic project to that of May Fourth.An open access version of this book was published with the support of the Swiss National Science Foundation. It can be found in the SUNY Open Access Repository at http://hdl.handle.net/20.500.12648/13924.